2013
DOI: 10.5152/eajm.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraarticular Bupivacaine and Levobupivacaine with Morphine and Epinephrine for Knee Arthroscopy

Abstract: Objective: To compare the efficacy of intraarticularly injected bupivacaine with levobupivacaine when administered in combination with morphine and adrenaline for post-operative analgesia and functional recovery after knee surgery. Materials and Methods:Sixty American Society of Anesthesiologists physical status I-II patients were randomized into three groups: Group B was administered 30 mL isobaric 0.5% bupivacaine, 2 mg morphine and 100 μg adrenaline, Group L was administered 30 mL 0.5% levobupivacaine, 2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For example, in a study that included 60 patients who underwent an arthroscopic knee surgery, intra-articular levobupivacaine combined with morphine and adrenaline or only bupivacaine decreased the postoperative duration of analgesic use and accelerated knee mobility. 26 On the other hand, some studies did not reveal any significant benefit to the different intra-articular anesthetic treatments. Solheim et al 30 compared the analgesic effect of intra-articular administration of saline or 5 mg morphine and found that there were no differences in pain intensity or pain relief at any time during the 48-hour observation period between morphine or saline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a study that included 60 patients who underwent an arthroscopic knee surgery, intra-articular levobupivacaine combined with morphine and adrenaline or only bupivacaine decreased the postoperative duration of analgesic use and accelerated knee mobility. 26 On the other hand, some studies did not reveal any significant benefit to the different intra-articular anesthetic treatments. Solheim et al 30 compared the analgesic effect of intra-articular administration of saline or 5 mg morphine and found that there were no differences in pain intensity or pain relief at any time during the 48-hour observation period between morphine or saline.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of various local anesthetic drugs into the joint space, either by a single injection or by a continuous infusion, to ameliorate postoperative pain following knee arthroscopy had been investigated, with some studies showing a beneficial effect while other studies did not. 26 , 30 , 34 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This hemodynamic profile is similar to various studies reviewed by us that have not reported any serious hemodynamic event in Fentanyl or Neostigmine group. [9][10][11][12][15][16][17][18][19][20][21][22] Kayacan et al [8] compared intra-articular Neostigmine to intra-articular Tramadol, Tenoxicam and Bupivacaine and found that compared to Bupivacaine group, Neostigmine had a relatively much stable hemodynamic profile, thus indicating that Neostigmine exercises a better hemodynamic control as compared to Bupivacaine. In the present study, Bupivacaine was used in all the three groups, however, hemodynamic profile of Neostigmine was no different from Bupivacaine alone group thus signifying that Neostigmine did not induce any additional hemodynamic change and thus was safe to be used even when used in combination with Bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of opioids and adrenergics demonstrate synergistic antinociceptive activity [14][15][16][17] that involves both α-adrenergic and β-adrenergic [18,19] components. For example, the addition of an adrenergic drug such as epinephrine or clonidine significantly reduces the amount of morphine required and its frequency of administration in the peri-and post-operative periods for a wide range of different types of surgeries [20][21][22][23][24][25][26][27][28][29]. The combination significantly decreases the need for intra-operative opiates [27,30], increases the duration of operative analgesia into the post-operative period [20][21][22][23][24]27,30,31].…”
Section: Introductionmentioning
confidence: 99%